2019
DOI: 10.1155/2019/8691398
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Method of Traction in a Bilateral Diaphyseal Femur Fracture in a Polytrauma Below-Knee Amputee

Abstract: While diaphyseal femoral shaft fractures are common, it is uncommon to see this injury in leg amputees. Traditionally, these fractures are internally fixed using a fracture table with reduction obtained by traction and adequate rotation exerted on a slightly abducted extremity. Special considerations need to be given in the management of patients with leg amputations. We report the case of a 24-year-old gentleman with bilateral diaphyseal femoral shaft fractures and a previous right below-knee amputation, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Other authors have reported modified traction techniques for amputees with proximal femur fractures. These include pulling traction through temporary transcutaneous pin-based mechanisms [12][13][14][15] , flexing the knee to fit in an "inverted boot" [16][17][18] , skin traction using elastic adhesive tape 19,20 , and simply providing manual traction 21 . When reduction cannot be achieved using noninvasive or minimally invasive techniques, open reduction may be necessary 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported modified traction techniques for amputees with proximal femur fractures. These include pulling traction through temporary transcutaneous pin-based mechanisms [12][13][14][15] , flexing the knee to fit in an "inverted boot" [16][17][18] , skin traction using elastic adhesive tape 19,20 , and simply providing manual traction 21 . When reduction cannot be achieved using noninvasive or minimally invasive techniques, open reduction may be necessary 22 .…”
Section: Discussionmentioning
confidence: 99%